Theoretical study on the optical properties of a phase change material blind in a double skin facade system - Li, Yilin; Peng, Yuke; Jing, Huaiwang; Fu, Sipeng (Frontiers in Built Environment, 2023)
Phase change material (PCM) blind, as a type of thermal energy storage device in building, has proved to be applicable in double skin façade (DSF) systems for mitigating the overheating problems in summer. However, there is lack of research information on the optical properties of PCM blind in a DSF system. In order to reveal the impact of design parameters on the optical performance of PCM blind, this paper focuses on the theoretical study of the optical properties of a PCM blind. Influences of slat inclination angle, ratio of slat distance to slat width, and slat surface material on the optical properties of the PCM blind system are discussed. The results show that with the increase of the slat inclination angle, the direct transmittance decreases, the direct absorption increases first and then decreases, and the diffuse absorption increases gradually. With the increase of the ratio of slat distance to slat width of blinds, the direct absorption decreases slowly at first, and then drops sharply when it reaches a critical point. No matter how the ratio of slat distance to slat width changes, the direct absorption is obviously greater than the diffuse absorption, while the direct transmittance is less than the diffuse transmittance. With the increase of the reflectance of the slat surface material, the direct absorption and diffuse absorption of the slat show a decreasing trend.